Antifungal susceptibility of Aspergillus spp. isolated from coffee beans of Los Santos Coffee Region, Costa Rica - Jaikel Víquez, Daniela (2026)
The indiscriminate use of fungicides in agricultural crops is considered one of the most important causes of antifungal resistance. Hence, it is our interest to contribute to the knowledge of antifungal resistance, within the framework of One Health. The results will be useful to define appropriate policies in the use of these drugs both in the clinical area and in agriculture. Thus, the susceptibility patterns of 187 Aspergillus spp. (A. flavus [n = 46], A. fumigatus [n = 8], A. insuetus [n = 1]; A. niger [n = 85], A. tamarii [n = 34] and Aspergillus section Versicolores [n = 13]), isolated from coffee beans from the Los Santos coffee-growing region in Costa Rica, were evaluated for amphotericin B (AMB), itraconazole (ITZ) and voriconazole (VRC); using the Clinical and Laboratory Standards Institute (CLSI) broth microdilution M38 guideline. The mean minimal inhibitory concentration (MIC) for AMB was 2.77 ± 3.19 μg mL-1, 0.29 ± 0.26 μg mL-1 for ITZ, and 1.14 ± 2.68 μg mL-1 for VRZ. Based on the CLSI guidelines, 15.2 % of A. flavus, 75.0 % of A. fumigatus and 3.5 % of the A. niger were classified as non-wild type for AMB; 4.3 % of the A. flavus/oryzae and 25.0 % of the A. fumigatus were classified as non-wild type for VRC. ITZ presented the lowest MIC distribution, and the isolates were classified as wild-type strains. The results show a high susceptibility to ITZ, moderate to VRC (treatment of choice for invasive aspergillosis) and low susceptibility to AMB.